التعددية الحزبية في الحركة الوطنية الجزائرية واثرها في بلورة مطلب الاستقلال - شرايطة, فائزة; حاج أحمد, عائشة (جامعة الوادي - University of Eloued, 2023)
عرفت الجزائر التعددية الحزبية منذ مطمع القرن العشرين في شكل تيا ارت سياسية ذات أبعاد حزبية؛ تمثلت فيما عرف بالحركة الوطنية ( ،)9191 - 9191إذ ظهرت في الساحة السياسية الجزائرية العديد من الأحزاب المختلفة الأيديولوجيات، منها: التيار الاستقلالي، التيار الإدماجي، التيار الإصلاحي، والحزب الشيوعي؛ ورغم الاختلاف في الأسلوب الخاص بهم لمتخمص من الهيمنة الاستعمارية الفرنسية، إلا أنهم رغم المجهودات المبذولة لتحقيق الاستقلال، نجدها لم تستطع تحقيقه نتيجة تعنت الجانب الفرنسي في ضد الوطنيين؛ ورغم ذلك فقد ساهمت في بلورة مطلب الاستقلال ليستمر الوضع حتى اندلاع الثورة التحريرية الجزائرية الكبرى Algeria has known partisan pluralism since the beginning of the twentieth century in the form of political currents with partisan dimensions represented by the national movement (1919-1954), as many parties with different ideologies appeared in the Algerian political arena, including: the independence movement, the integrationist movement, the reformist movement and the Communist Party, despite The difference is in their own method to get rid of French colonial domination, but despite the efforts made to achieve independence, we find that it was unable to achieve it as a result of the intransigence of the French side in its dealings against the patriots, despite that it contributed to crystallizing the demand for independence so that the situation would continue until the outbreak of the great Algerian liberation
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: التعددية الحزبية – الحركة الوطنية – التيار الاستقلالي- التيار الإدماجي- التيار الإصلاحي – الحزب الشيوعي; partisan pluralism - the national movement - the independence movement - the assimilationist movement - the reformist movement - the Communist Party